Perbandingan Strategi Pemasaran Benih Jagung Malaysia dan Indonesia - Listyarini, Indah; Suhaimee, Syahrin; Thamrin, Muhammad; Gurning, Riris Nadia (JURNAL AGROPLASMA, 2024)
This research aims to analyze the corn seeds marketing strategies for Indonesianand Malaysian. The data used in this research is secondary data. The method usedin this research is descriptive and SWOT analysis. Both countries (Indonesia andMalaysia) has a different way of handling corn seed marketing strategies, eachcountry has its advantages and disadvantages in handling the marketing strategy(forcornseed). Keywords: seed, corn, marketing strategy